2000
DOI: 10.1002/(sici)1097-0215(20000601)86:5<702::aid-ijc16>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of natural and induced human antibodies to MUC1 mucin with MUC1 peptides andn-acetylgalactosamine (GalNAc) peptides

Abstract: Antibodies (Abs) to MUC1 occur naturally in both healthy subjects and cancer patients and can be induced by MUC1 peptide vaccination. We compared the specificity of natural and induced MUC1 Abs with the objective of defining an effective MUC1 vaccine for active immunotherapy of adenocarcinoma patients. Serum samples, selected out of a screened population of 492 subjects for their high levels of IgG and/or IgM MUC1 Abs, were obtained from 55 control subjects and from 26 breast cancer patients before primary tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(35 citation statements)
references
References 29 publications
0
33
2
Order By: Relevance
“…The MUC1 mucin is heavily O-glycosylated in a large 20 amino acid tandem repeated region, which is aberrantly glycosylated in cancer (20) and can be detected in serum of late stage cancer patients (21;22). Man is in general immunologically tolerant to the MUC1 tandem repeat protein core and its normal glycosylated forms (20;23), although, several studies have shown that up to 10–15% of healthy controls and cancer patients have antibody reactivity to MUC1 peptides as detected by ELISA assays; however, the detected levels are very low and have led to contradictory results by different investigators (2427). We recently identified an immunodominant O-glycopeptide epitope (Tn/STn-MUC1) that results from aberrant glycosylation and for which there does not appear to be immunological tolerance (2830) (See Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The MUC1 mucin is heavily O-glycosylated in a large 20 amino acid tandem repeated region, which is aberrantly glycosylated in cancer (20) and can be detected in serum of late stage cancer patients (21;22). Man is in general immunologically tolerant to the MUC1 tandem repeat protein core and its normal glycosylated forms (20;23), although, several studies have shown that up to 10–15% of healthy controls and cancer patients have antibody reactivity to MUC1 peptides as detected by ELISA assays; however, the detected levels are very low and have led to contradictory results by different investigators (2427). We recently identified an immunodominant O-glycopeptide epitope (Tn/STn-MUC1) that results from aberrant glycosylation and for which there does not appear to be immunological tolerance (2830) (See Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are of particular relevance in case of MUC1, since in contradiction to previous assumptions this mucin seems to be more densely O-glycosylated on tumor cells compared to normal cells, though with truncated glycans related to the Tn and T antigens and their sialylated derivatives [11]. It is not surprising, accordingly, that natural and experimentally induced antibody responses in humans are more directed to glycosylated MUC1 epitopes [12]. On the other hand, antibodies generated to the non-glycosylated MUC1 repeat peptide were largely unable to bind the natural, tumor-associated glycoform [12].…”
Section: Why Muc1?mentioning
confidence: 75%
“…It is not surprising, accordingly, that natural and experimentally induced antibody responses in humans are more directed to glycosylated MUC1 epitopes [12]. On the other hand, antibodies generated to the non-glycosylated MUC1 repeat peptide were largely unable to bind the natural, tumor-associated glycoform [12]. So, cancer immunologists end up with the challenge to design a MUC1-based cancer vaccine that, on the one hand, induces immune responses to the natural, heavily O-glycosylated target, but on the other, allows for active processing and MHC presentation of glycopeptides to finally elicit strong and long lasting responses to the glycotopes on tumor cells.…”
Section: Why Muc1?mentioning
confidence: 99%
“…These self-molecules trigger B cell activation usually because of aberrant expression, mislocalization, sequencing errors 107,108 , and/or altered post-translational modifications 109 . Thus, autoantibodies can lend interesting insights into disease processes.…”
Section: Resultsmentioning
confidence: 99%